2013
DOI: 10.1172/jci65952
|View full text |Cite|
|
Sign up to set email alerts
|

Osteocalcin regulates murine and human fertility through a pancreas-bone-testis axis

Abstract: The osteoblast-derived hormone osteocalcin promotes testosterone biosynthesis in the mouse testis by binding to GPRC6A in Leydig cells. Interestingly, Osteocalcin-deficient mice exhibit increased levels of luteinizing hormone (LH), a pituitary hormone that regulates sex steroid synthesis in the testes. These observations raise the question of whether LH regulates osteocalcin's reproductive effects. Additionally, there is growing evidence that osteocalcin levels are a reliable marker of insulin secretion and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(149 citation statements)
references
References 38 publications
6
139
2
2
Order By: Relevance
“…Interleukin 6 has been shown to inhibit the differentiation of rat stem Leydig cells leading to downregulation of steroidogenic enzymes and lower serum testosterone levels [34]. Previous studies have suggested that osteoblast-derived OC may stimulate testosterone production [16]. Serum OC concentrations were lower in males with childhood-onset obesity than in controls, but did not correlate with serum testosterone concentrations in the males with childhood-onset obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interleukin 6 has been shown to inhibit the differentiation of rat stem Leydig cells leading to downregulation of steroidogenic enzymes and lower serum testosterone levels [34]. Previous studies have suggested that osteoblast-derived OC may stimulate testosterone production [16]. Serum OC concentrations were lower in males with childhood-onset obesity than in controls, but did not correlate with serum testosterone concentrations in the males with childhood-onset obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests the presence of endocrine regulation between bone and testes beyond sex steroids – the bone-testis axis. Osteoblast-derived uncarboxylated osteocalcin (OC) stimulates testosterone production in the testes in mice [16]. In humans, serum total OC levels correlate positively with testosterone levels in adult men [17, 18] and pubertal boys [19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it appears that the reproductive function of OC translates to humans, with the identification of a positive association between OC and testosterone serum levels in the general population, patients with bone disorders and patients with T2DM (Hannemann et al 2013, Kanazawa et al 2013. Furthermore, two subjects were identified from a cohort of patients displaying testicular failure who harboured a heterozygous missense variant in one of the transmembrane domains of GPRC6A, giving credence to a role of OC function in humans (Oury et al 2013;reviewed in Karsenty & Oury (2014)). …”
Section: Clinical Evidence: Oc and Metabolism/fertilitymentioning
confidence: 99%
“…GPRC6A has been shown to be integral in the promotion of b-cell proliferation during development and adulthood via OC, thus highlighting GPRC6A as an important receptor for skeletal-tissue-mediated energy regulation via the pancreas (Pi et al 2011, Wei et al 2014a. Most recently, Oury et al (2013) demonstrated that OC acts via a pancreas-bone-testis axis, such that OC-stimulated testosterone synthesis is positively regulated by insulin signalling in osteoblasts and is independent of luteinising hormone (LH). No connection between Ptprv K/K and Oc K/K mice in osteoblast-stimulated oestradiol production was identified, illustrating that the regulatory mechanisms of fertility of male and female mice are vastly distinct (Oury et al 2011).…”
Section: Male Fertility and The Discovery Of The Oc Receptormentioning
confidence: 99%
“…Osteocalcin is a bone-secreted hormone regulating the secretion of insulin, adiponectin and testosterone in rodents and humans [1][2][3][4]. Furthermore, lower serum osteocalcin was associated with greater insulin resistance in type 2 diabetes patients [5,6], metabolic syndrome (MetS) [7,8] and vascular calcifications [9].…”
Section: Introductionmentioning
confidence: 99%